Changing Perceptions of Institutions and Standard of Living in Iraq - Ansar, Saniya; Celiku, Bledi; Klapper, Leora; Mansour, Wael (World Bank, Washington, DC, 2021)
The history of Iraq over the past decade is a stark example of increasing vertical and horizontal inequalities, preceding and following a period of violent conflict. This paper uses a cross-section of individual-level nationally representative survey data to study relationships around how adults in Iraq report confidence in national institutions, quality of life, and quality of service delivery. The findings show that positive perceptions across these categories declined during ISIS-control and have slowly picked up in recent years. Men are more likely than women in the post-ISIS period to report lower country leadership approval ratings, a weaker standard of living, and depressed job prospects. The analysis finds that self-identified Shias, Kurds, and adults living in Baghdad are significantly more likely to have a poorer quality of life, compared with Sunnis, in the post-ISIS period. Nearly all ethno-religious groups, in all periods, perceive the government to be corrupt.